Chronic toxicity of selected polycyclic aromatic hydrocarbons to algae and crustaceans using passive dosing. (14th July 2016) - Bragin, Gail E.; Parkerton, Thomas F.; Redman, Aaron D.; Letinksi, Daniel J.; Butler, Josh D.; Paumen, Miriam Leon; Sutherland, Cary A.; Knarr, Tricia M.; Comber, Mike; den Haan, Klaas
Abstract: Because of the large number of possible aromatic hydrocarbon structures, predictive toxicity models are needed to support substance hazard and risk assessments. Calibration and evaluation of such models requires toxicity data with well‐defined exposures. The present study has applied a passive dosing method to generate reliable chronic effects data for 8 polycyclic aromatic hydrocarbons (PAHs) on the green algae Pseudokirchneriella subcapitata and the crustacean Ceriodaphnia dubia . The observed toxicity of these substances on algal growth rate and neonate production were then compared with available literature toxicity data for these species, as well as target lipid model and chemical activity‐based model predictions. The use of passive dosing provided well‐controlled exposures that yielded more consistent data sets than attained by past literature studies. Results from the present study, which were designed to exclude the complicating influence of ultraviolet light, were found to be well described by both target lipid model and chemical activity effect models. The present study also found that the lack of chronic effects for high molecular weight PAHs was consistent with the limited chemical activity that could be achieved for these compounds in the aqueous test media. Findings from this analysis highlight that variability in past literature toxicity data for PAHs may be complicated by both poorly controlled exposures and photochemical processes that can modulate both exposure and toxicity. Environ Toxicol Chem 2016;35:2948–2957. © 2016 SETAC